What affect perceived ease of ICT usage: the case of village development and security committee members in Malaysia - Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Abu Hassan, Musa; Alby, Jeffrey Lawrence D'Silva (American-Eurasian Network for Scientific Information, 2011)
Rural development and ICT cannot be separated in this modern days. Malaysia is well known with its effort to strengthen its ICT development and interestingly the rural community is one of the main targets of such developments. Rural community must be encouraged to continuously use ICT in their daily life. However, before the community is encouraged to use the ICT, are their leaders Village Development and Security Committee Members use ICT? How they perceive the ease of ICT usage? What are the factors that influence Village Development and Security Committee members perception towards ease of use in using ICT? This paper attempts to answer the above question which will uncover factors that determining Village Development and Security Committee members perceived ease of ICT usage. This is a quantitative study where a set of questionnaire was employed for the data collection process. A total of 240 respondents among Village Development and Security Committee members were selected. The respondents were selected from four states in Malaysia namely Kedah, Terengganu, Perak and Johor. Results from data analyses revealed that job relevance, self efficacy, compatibility and attitude recorded a high and significant relationship with perceived ease of ICT usage. Further insight into the analysis unveiled job relevance as the most significant factor towards perceived ease of ICT usage. In order to create a positive perceive ease of ICT usage among the Village Development and Security Committee, it is recommended that ICT learning session with the assistance of related agencies officers should be established within all the Village Development and Security Committee Members. On top of it, language is among the top matters that should be stressed in order to enhance Village Development and Security Members perceived ease of ICT usage.